Implementation of Mobile Samsat Services in Improving the Quality of Public Services in Bapenda Southeast Sulawesi Province - Mayunita*, Sry; Wijaya, Andy Arya Maulana; Suhada, Suhada; Jahami, Jasti (Universitas Syiah Kuala, 2024)
Mobile Samsat is an innovation launched by the Southeast Sulawesi Bapenda as a form of innovation in the field of public services with the aim of increasing regional revenues sourced from the re-registration of Motor Vehicle Tax (PKB). This research aims to determine the implementation of Mobile Samsat services in improving the quality of public services in Bapenda Southeast Sulawesi. The research method used is a descriptive research method with a qualitative approach. Data collection techniques use three methods, namely interviews, observation and documentation studies. The data sources in this research consist of two, namely primary data sources and secondary data sources. The data analysis technique uses three stages, namely data reduction, data presentation, and drawing conclusions. The research results show that the overall implementation of Mobile Samsat services is running effectively. Communication variables that show that implementation has been effective. The resources variable shows that resources in overall implementation have been maximized, although there must be additional staff resources. The attitude or disposition variable of the implementer has shown a good attitude. The bureaucratic structure variable also shows the existence of Standard Operating Procedures (SOP) in the implementation of services.